2000
DOI: 10.1128/jvi.74.5.2443-2446.2000
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Transforming Growth Factor β1 Levels in Epstein-Barr Virus-Associated Diseases and Their Correlation with Virus-Specific Immunoglobulin A (IgA) and IgM

Abstract: Transforming growth factor ␤ (TGF-␤) is an immunosuppressive cytokine which can induce immunoglobulin A (IgA) switch and Epstein-Barr virus (EBV) replication in latently infected cells. Here we report elevated serum levels of TGF-␤ in various EBV-associated diseases correlating positively with EBV-specific IgA titers and negatively with IgM titers, suggesting a role for this cytokine in the pathogenesis of these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…6). The concentrations of circulating latent TGF-␤1 protein were consistent with values found in studies of infection with Epstein-Barr virus in humans; however, the quantity of circulating active TGF-␤1 protein was approximately 100-fold lower than that found in the same study (23) and was probably not biologically significant. Also, there was no significant difference among the quantities of active TGF-␤1 in the sera of the infected calves at each time point studied (t test, P Ͼ 0.05).…”
Section: Ncpbvdv Stimulates Ifn-␥ Responses In Vivosupporting
confidence: 74%
“…6). The concentrations of circulating latent TGF-␤1 protein were consistent with values found in studies of infection with Epstein-Barr virus in humans; however, the quantity of circulating active TGF-␤1 protein was approximately 100-fold lower than that found in the same study (23) and was probably not biologically significant. Also, there was no significant difference among the quantities of active TGF-␤1 in the sera of the infected calves at each time point studied (t test, P Ͼ 0.05).…”
Section: Ncpbvdv Stimulates Ifn-␥ Responses In Vivosupporting
confidence: 74%
“…The role of immunosuppressive effect of TGF-h in cancer progression has been well established (13,(25)(26)(27). In the present study, we have shown that, TRAMP-C2 tumors possess potent immunosuppressive power so that regular CD8 + T cells are unable to infiltrate into the tumor tissues.…”
Section: Discussionmentioning
confidence: 53%
“…TGF-β in neurons has also been reported in mice with experimental allergic encephalomyelitis (Fujinami, 2006;Issazadeh et al, 1998) and in rats with spinal cord injury (O'Brien et al, 1994). Although in vivo induction of TGF-β1 specifically in CNS neurons by virus infections has not been reported, TGF-β1 is produced or activated in other cell types by several virus infections [reviewed in (Fitzpatrick and Bielefeldt-Ohmann, 1999)], including Epstein-Barr virus (Xu et al, 2000), cytomegalovirus (Haagmans et al, 1997;Michelson et al, 1994), herpes simplex virus (Méndez-Samperio et al, 2000), human T-lymphotropic virus (HTLV)-I, human immunodeficiency virus (HIV) (Lotz and Seth, 1993;Wahl et al, 1991;Yamamoto et al, 1999), influenza virus (Schultz-Cherry andHinshaw, 1996) and yellow fever virus (Quaresma et al, 2006).…”
Section: Discussionmentioning
confidence: 99%